2005
DOI: 10.1007/s11250-005-4219-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Fertility According to the Postpartum Period in Crossbred Dual-Purpose Suckling Cows in the Tropics

Abstract: To determine the relationship between first service conception rate (FSC) and the postpartum period (PP), 6160 calvings from 2250 crossbred dual-purpose cows were analysed. The effects of breed predominance (BT: Bos taurus and BI: Bos indicus), season of service (dry, intermediate and humid), parity (1 or 2 and more), agroecological region (Sub-humid and Dry Tropical Forest) and milk production were studied. The postpartum period was grouped according to the calving-first service interval as G1 < or = 60 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…This might generally indicate that genetic differences between breeds in the incidence and types of AOC can result in differences in fertility parameters such as conception rate. 20 In addition, adaptation differences to the hot and humid tropical environment may account for the large difference between the local KK and the other three breeds. Under the hot and humid conditions, despite high rainfall that produces more forage, high humidity, and temperature, could cause stress and affect their reproductive functions by modifying the endocrine balance and altering the oviductal uterine environment that delays or interrupts embryo development.…”
Section: Figure 1 Ovary With Luteal Cyst From a Friesian Sahiwal Cowmentioning
confidence: 99%
See 1 more Smart Citation
“…This might generally indicate that genetic differences between breeds in the incidence and types of AOC can result in differences in fertility parameters such as conception rate. 20 In addition, adaptation differences to the hot and humid tropical environment may account for the large difference between the local KK and the other three breeds. Under the hot and humid conditions, despite high rainfall that produces more forage, high humidity, and temperature, could cause stress and affect their reproductive functions by modifying the endocrine balance and altering the oviductal uterine environment that delays or interrupts embryo development.…”
Section: Figure 1 Ovary With Luteal Cyst From a Friesian Sahiwal Cowmentioning
confidence: 99%
“…Under the hot and humid conditions, despite high rainfall that produces more forage, high humidity, and temperature, could cause stress and affect their reproductive functions by modifying the endocrine balance and altering the oviductal uterine environment that delays or interrupts embryo development. 20 According to, 21 dairy cows with COD have been reported to have increased heat shock protein (Hsp27) expressions theca cells in relation to tertiary follicles of normal cycling cows, indicating the possible link between COD occurrence and heat stress in cattle. Zebu cows (Bos indicus) and their crossbreeds show lower levels of milk production and better adaptation to the adverse tropical environment, and hence show lesser effects on the postpartum body condition but a higher reproductive efficiency than the predominantly Bos taurus cows.…”
Section: Figure 1 Ovary With Luteal Cyst From a Friesian Sahiwal Cowmentioning
confidence: 99%
“…This is not surprising as these cows were selected from a herd of cattle with a record of very high calving rate, >92% in the previous year, compared with the other breeds, dairy FRX (56.6%), BRFX (33.3%), and BRX (43.5%). This generally might indicate the presence of genetic differences among breeds in the incidence and types of abnormal ovarian cycles that can result in differences in fertility parameters such as conception rate (Perea-Ganchou et al 2005). In addition, adaptation differences to the hot humid tropical environment may account for the big difference between the local KKX and the other three breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Under the hot and humid condition, despite high rainfall that produces more forage, high humidity and temperature cause stress and affect the reproductive function through modifying endocrine balance and altering oviductaluterine environment that delays or interrupts embryo development (Perea-Ganchou et al 2005). Zebu cows (Bos indicus) and their crossbreeds have lower levels of milk production and better adaptation to adverse tropical environment and hence show lower postpartum body condition losses but a higher reproductive efficiency than the predominantly B. taurus cows (Perea-Ganchou et al 2005) Abnormal luteal function in lactating cows have been reported to be associated with reduced pregnancy rate, whereby cows with normal progesterone profiles showed significantly higher pregnancy rate than cows with abnormal profiles (87% vs 33%) following AI (Hommeida et al 2004). Moreover, a significantly higher AI submission rate, conception rate, and pregnancy rate between 44 and 100 days postpartum were reported in dairy cows with normal ovarian cycle in the first 44 days postpartum than those with prolonged luteal phases (Shrestha et al 2004a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Mafriwal showed higher milk production and weight gain compared to indigenous breeds for example, Kedah Kelantan (KK). However, its fertility was shown to suffer from heat stress [3,4]. …”
Section: Introductionmentioning
confidence: 99%